2016
DOI: 10.1051/0004-6361/201526271
|View full text |Cite
|
Sign up to set email alerts
|

The sulfur depletion problem: upper limits on the H2S2, HS·2, and S2gas-phase abundances toward the low-mass warm core IRAS 16293-2422

Abstract: Context. A fraction of the missing sulfur in dense clouds and circumstellar regions could be in the form of three species not yet detected in the interstellar medium: H 2 S 2 , HS . 2 , and S 2 according to experimental simulations performed under astrophysically relevant conditions. These S-S bonded molecules can be formed by the energetic processing of H 2 S-bearing ice mantles on dust grains, and subsequently desorb to the gas phase. Aims. The detection of these species could partially solve the sulfur depl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 52 publications
1
33
1
Order By: Relevance
“…These findings stimulated recent efforts to observe H 2 S 2 , HS 2 , and S 2 in the gas phase toward the low-mass warm core IRAS 16293-2422(Martín-Doménech et al 2016. Estimated upper limit abundances of these molecules are up to two orders of magnitude lower than the H 2 S abundance in the source.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…These findings stimulated recent efforts to observe H 2 S 2 , HS 2 , and S 2 in the gas phase toward the low-mass warm core IRAS 16293-2422(Martín-Doménech et al 2016. Estimated upper limit abundances of these molecules are up to two orders of magnitude lower than the H 2 S abundance in the source.…”
Section: Introductionmentioning
confidence: 88%
“…It is believed that the desorption of grain mantle species into the gas phase, for example after warming by a protostar or sputtering by energetic cosmic ions, gives an important contribution to the gas phase composition (Modica & Palumbo 2010;Palumbo et al 2008). As outlined by Martín-Doménech et al (2016) it seems plausible that an important fraction of the observed S-bearing gas phase species is released from grains because molecules such as H 2 S, SO 2 , OCS, SO, H 2 CS, HCS + , and NS have abundances that cannot A&A 604, A68 (2017) be explained with gas-phase-only chemical models (Doty et al 2004;Viti et al 2004;Wakelam et al 2011;Woods et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…1-89;Papousek & Aliev 1982), can produce comparison to experiment to better than 5.0 cm −1 for vibrational frequencies and 30 MHz for rotational constants Fortenberry et al 2012bFortenberry et al , 2014aHuang et al 2013a;Zhao et al 2014;Kitchens & Fortenberry 2016). Such a CcCRE PES computed for HSS has produced useful spectroscopic data (Peterson et al 2008) to aid in the interstellar search for this simple, yet hidden disulfide radical (Martín-Doménech et al 2016). However, the spectral data set is still somewhat incomplete, and additional corroboration for the known theoretical or even experimental data would give astronomers more trust in utilizing theoretical data for comparison to interstellar spectra.…”
Section: Introductionmentioning
confidence: 98%
“…For instance, a recent survey of the low-mass warm core IRAS 16293-2422 returned a non-detection for this radical and inconclusive results about its possible interstellar abundance (Martín-Doménech et al 2016). This is perplexing since HSS is believed to exist in relatively high abundances in icy grains and may be even be the most common form of sulfur in such environnments, even more than H 2 S based on observations of the Hale-Bopp comet (Bockelée-Morvan et al 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation